Peran Orang Tua Dalam Membentuk Motivasi Belajar Anak Di Usia Dini - Firmansyah, Fitri Awan Arif; Tyas, Devi Marganing (Universitas Pahlawan Tuanku Tambusai, 2025)
This paper discusses the role of parents in improving children’s learning motivation. The children refered to in this paper are children of primary school age (SD/MI) is those aged 3 years to 6 years. Parents have of very important role in the education of their children among them as a motivator. In this case the parents should always give encouragement to their children to have a passion in learning, especially in home study as a supporter of successful achiement in school. The efforts that can be done by parents in improving motivation to learn children include: 1) knowing the results, 2) providing rewards and punishments, 3) provide the necessary tools or facilities. Parents as educators should always pay attention to child’s personal development as a determinant in the treatment of education in accordance with the period or level of age and ability to think chil